Upaya Pelestarian Tari Piriang Pandai Sikek Di Nagari Pandai Sikek Kabupaten Tanah Datar Provinsi Sumatera Barat - Zikriyah, Putri; Maghfirah, Auliana Mukhti; Suherni Suherni; Fikri, Muhammad (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to discuss the Piriang Pandai Sikek Dance in Pandai Sikek Village, Tanah Datar Regency, West Sumatra Province. The research method used is a qualitative approach with a descriptive analysis. All data obtained, both written and field data, are described and then analyzed according to the proposed research problem. The theory used is the textual theory (form, technique, and style) proposed by Y. Sumandiyo Hadi, and the preservation theory proposed by Edi Sedyawati. The results indicate that the Piriang Pandai Sikek Dance is a traditional dance depicting the routines of animals and the farming habits of the Pandai Sikek community. This dance is a typical Pandai Sikek dance that can only be performed by the native Pandai Sikek community. To ensure this dance is not lost, preservation efforts are being carried out by providing training to the younger generation in Pandai Sikek Village.